Median Nerve Injury in Ultrasound-Guided Hydrodissection and Corticosteroid Injections for Carpal Tunnel Syndrome - Hsu, Yi-Chih; Yang, Fu-Chi; Hsu, Hsian-He; Huang, Guo-Shu (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose Permanent nerve damage after corticosteroid injection has been suggested when symptoms of median nerve injury (MNI) are irreversible. We assess the outcomes of MNI and their association with ultrasonography (US)-guided hydrodissection and the following corticosteroid injection for symptomatic carpal tunnel syndrome (CTS).Methods US-guided hydrodissection and the following corticosteroid injections were administered to 126 CTS patients. Occurrence of MNI, clinical data, and post-hydrodissection findings were evaluated. Post-hydrodissection findings included vascular injury during hydrodissection, altered echogenicity, reduced flattening ratio, and increased cross-sectional area of the MN at the inlet of the carpal tunnel (MN-CSA-Inlet) on ultrasonography after hydrodissection. The relevance of MNI with respect to these clinical data and findings was determined. The outcome was rated using Boston Carpal Tunnel Syndrome Questionnaire (BCTQ) scores.Results Nine patients suffered MNI (incidence, 7.1 %) but improved significantly at follow-up. Clinical data and vascular injury during hydrodissection, altered echogenicity, and reduced flattening ratio after hydrodissection were unrelated to prolonged transient MNI (p > 0.05). MNI was significantly associated with increased CSA (p = 0.005). A CSA increase > 2 mm2 after hydrodissection yielded the greatest performance (0.979) for MNI in the receiver operating characteristic analysis. Decreases in BCTQ scores after injection did not differ significantly between groups with and without MNI (p > 0.05).Conclusion MNI during hydrodissection may be reversible. MNI is indicated by an increase in MN-CSA-inlet immediately after hydrodissection.
Keywords: carpal tunnel syndrome; injuries; median nerve; steroids; ultrasonography